2021
DOI: 10.3390/healthcare9040479
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Procedural Lumbar Neuraxial Ultrasound—A Systematic Review of Randomized Controlled Trials and Meta-Analysis

Abstract: A pre-procedural ultrasound of the lumbar spine is frequently used to facilitate neuraxial procedures. The aim of this review is to examine the evidence sustaining the utilization of pre-procedural neuraxial ultrasound compared to conventional methods. We perform a systematic review of randomized controlled trials with meta-analyses. We search the electronic databases Medline, Cochrane Central, Science Direct and Scopus up to 1 June 2019. We include trials comparing a pre-procedural lumbar spine ultrasound to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Previous case reports of successful neuraxial anesthesia in obstetrical patients with intrathecal baclofen pumps or spinal cord stimulators have been documented. 4,5 In 4 out of 5 patients described in case reports, lumbar neuraxial ultrasonography was used preoperatively to aid in placement of spinal blockade in patients with preexisting intrathecal baclofen pumps and spinal cord stimulators. 4,5 However, the approaches to neuraxial ultrasound examinations were not well described in the case reports, and ultrasound images were unavailable for review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous case reports of successful neuraxial anesthesia in obstetrical patients with intrathecal baclofen pumps or spinal cord stimulators have been documented. 4,5 In 4 out of 5 patients described in case reports, lumbar neuraxial ultrasonography was used preoperatively to aid in placement of spinal blockade in patients with preexisting intrathecal baclofen pumps and spinal cord stimulators. 4,5 However, the approaches to neuraxial ultrasound examinations were not well described in the case reports, and ultrasound images were unavailable for review.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In 4 out of 5 patients described in case reports, lumbar neuraxial ultrasonography was used preoperatively to aid in placement of spinal blockade in patients with preexisting intrathecal baclofen pumps and spinal cord stimulators. 4,5 However, the approaches to neuraxial ultrasound examinations were not well described in the case reports, and ultrasound images were unavailable for review. There are no existing case reports of patients with indwelling spinal hardware that also describe the methodology or include images of lumbar neuraxial ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performing neuraxial anesthesia in obstetric patients with spina bifida can be challenging because of increased technical difficulty and the risk of neurologic complications. Recent systematic reviews have indicated that the lumbar US can provide anatomic information indicating the depth of the epidural space, the identity of a given intervertebral level, the location of the midline, and interspinous or interlaminar spaces [ 3 , 4 ]. In addition, lumbar US can help to improve clinical outcomes of neuraxial anesthesia [ 5 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preprocedural imaging of the lumbar spine by computed tomography (CT) or magnetic resonance imaging (MRI) can be crucial for determining the feasibility of neuraxial anesthesia, but there are risks [ 3 , 4 ], and these modalities can be expensive. Lumbar ultrasonography (US) can be used easily, safely, and consistently to facilitate neuraxial procedures for pregnant women [ 3 , 4 ]. We present four cases of pregnant women with spina bifida who underwent lumbar US before obstetric analgesia or anesthesia.…”
Section: Introductionmentioning
confidence: 99%